METODE KERJA KELOMPOK SEBAGAI UPAYA PENINGKATAN KOMPETENSI GURU DALAM MENYUSUN SOAL TES SEMESTER DI SDN KALIBANTENG KULON 02 SEMARANG - Sugiwanti, Sugiwanti (Jurnal Inovasi Pembelajaran di Sekolah, 2021)
The act of making questions as an assessment instrument cannot be carried out arbitrarily, to improve the quality of teachers in making questions, it is necessary to know about making tests. However, it was found that there were many written test questions for the semester that the teachers of SDN Kalibanteng Kulon 02 Semarang City did not comply with the rules for writing questions. Of the 18 teachers there are only 5 teachers or 28% of teachers who are able to make written test questions according to the rules. Written test items that are not correct from the point of view of the rules for writing questions must be corrected or replaced with new items. This of course requires the role of the principal by carrying out academic supervision activities that can be done using group techniques through the Group Work method which can be done by holding group discussions. This is intended to answer problems 1) How is the implementation of the group work method as an effort to increase teacher competence in preparing semester test questions at SDN Kalibanteng Kulon 02 Semarang City for the 2020/2021 academic year?. 2) Can the implementation of the group work method improve teacher competence in preparing semester test questions at SDN Kalibanteng Kulon 02 Semarang City for the 2020/2021 school year? These problems are discussed through school action research which is carried out through 2 cycles with each cycle the stages are planning, action, observation and reflection. The results showed: 1) The implementation of the group work method as an effort to increase teacher competence in preparing semester test questions was carried out by dividing groups of teachers under the supervision of the principal, each group was given material on the preparation of a good semester test and according to the rules previously given. an explanation by the supervisor, each group reviewed and discussed how to prepare a good semester test based on the results of the test preparation that had been made by each member, the results of the group discussion were then presented and commented on by other groups. 2) The implementation of the group work method can improve teacher competence in preparing semester test questions, this can be seen from the increase in the results of teacher professionalism in classroom administration management per cycle where in the first cycle there are 12 teachers or 66% and in the second cycle there are 17 teachers or 94 %. These results indicate that these results are in line with expectations. An increase also occurred in teacher activities in participating in mini workshops where in the first cycle there were 11 teachers or 61% and in the second cycle there were 16 teachers or 89%. The increase in the implementation of mini workshops is an effective way for school principals to improve the ability of teachers to develop learning tools.